Miniaturization Techniques using Magnetic Materials for Broadband Antenna Applications. - Durbha, Ravi.; Afsar, Mohammed N. (Tufts University. Tisch Library., 2019)
This paper investigates the instrumentation necessary to analyze frequency-dependent complex parameters of solid magnetic materials based on T/R based waveguide measurement technique proposed by W. B. Weir. Based on magnitude and phase values of transmission and reflection coefficients measured using vector network analyzer, complex permittivity and permeability are calculated using the expressions defined. Equations necessary for calculating the complex parameters as a function of frequency with required step size are derived from the experimental results. To validate mathematical expressions developed for composite magnetic materials, design of a compact 2-18GHz Cavity Backed Spiral Antenna using off-the-shelf magnetic materials is presented. The electrical performance of the cavity along with stack of high contrast magnetic materials of varying dimensions are modeled and simulated in Ansys HFSS software. (c) 2019 IEEE.